(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
An 8 weeks feeding trial was conducted to evaluate the nutritive contribution of red kidney bean (phaseoulus vulgaris) seed meal on growth performance, carcass and internal organ characteristics and economics of production of broiler chickens. Two hundred (Anak-2000) white strain day old broiler chicks were weight and assigned to five groups of forty chicks each. Each group was further divided into four groups of ten birds per replicate in completely randomized design. Five diets were formulated using differently processed Red kidney bean seed meal (Phaseoulus vulgaris) at 0% in the control (T1) and 25% levels of inclusion for Raw (RRKBSM), Toasted (TRKBSM), boiled (BRKBSM) and Dehaulled (DRKBSM) respectively. Feed and water were given ad-libtum daily throughout the feeding trial. The growth performance showed significant (P<0.05) difference for all the parameters. However, there were significance (P<0.05) for live weight, dressed weight, plucked weight, breast weight, back, thigh, drumstick, shank, kidney and lungs. Similarly cost/kg feed was higher in T4 (N 449.91) and lowest in T2 (N 424.20). Feed cost/kg weight gain was higher in T5 (N 440.93/kg) gain and lowest feed cost/kg gain was on T4 (N 308.14/kg) gain. From the foregoing, it implies that RKBSM is a potential feed resource and could be included in diets of broiler chickens when differently processed up to 25% inclusion level as protein source in broiler chicken diet for growth and performance.